Ferroptosis in Cancer Treatment: Another Way to Rome - Wu, Yinan; Yu, Chengcheng; Luo, Meng; Cen, Chen; Qiu, Jili; Zhang, Suzhan; Hu, Kaimin (Frontiers in Oncology, 2020)
Ferroptosis is a newly described type of programmed cell death and intensively related to both maintaining homeostasis and the development of diseases, especially cancers. Inducing ferroptosis leads to mitochondrial dysfunction and toxic lipid peroxidation in cells, which plays a pivotal role in suppressing cancer growth and progression. Here, we reviewed the existing studies about the molecular mechanisms of ferroptosis involved in different antitumor treatments, such as chemotherapy, targeted therapy, radiotherapy, and immunotherapy. We focused in particular on the distinct combinatorial therapeutic effects such as the synergistic sensitization effect and the drug-resistance reversal achieved when using ferroptosis inducers with conventional cancer therapy. Finally, we discussed the challenges and opportunities in clinical applications of ferroptosis. The application of nanotechnolgy and other novel technologies may provide a new direction in ferroptosis-driven cancer therapies.